ISFT - INTERNATIONAL SCHOOL OF FINANCE TECHNOLOGY AND SCIENCE - Raimjanova Makhbuba Nomanovna (Journals Park Publishing, 2024)
The International School of Financial Technology and Sciences (ISFT) stands at the forefront of revolutionizing financial education by integrating cutting-edge technology with traditional financial principles. This article provides an in-depth exploration of ISFT's mission, programs, research initiatives, and contributions to the global financial landscape. By fostering a dynamic learning environment and promoting innovation, ISFT is shaping the future of financial education and technology.
Keywords: ISFT, financial education, technology, innovation, research.